Expression of variant isoforms of the tyrosine kinase SYK differentially regulates cervical cancer progression through PI3K/AKT pathway - Bingjie Lin; Qixin Wang; Xin Wang; Hongjian Wei; Xiaojing Nie; Li Li; Yonghua Shi (Scientific Reports)
Abstract Invasion and metastasis are the main reasons for the poor prognosis of patients with cervical cancer(CC). SYK is closely related to tumor development. However, the functions of its two isoforms, SYK (L) or SYK (S), are not fully understood to date. In this study, we investigated their biologic functions and possible prognostic values in CC. qRT-PCR was performed to detect the expression of SYK and two variant isoforms in cervical cancer tissues and cells. The association of SYK(L) and SYK(S) with Clinical pathological parameters were evaluated. The migration and invasion was detected by scratch assay and transwell. Western blot was conducted to measure the changes of epithelial mesenchymal transition (EMT)-related markers and PI3K/AKT signaling pathway proteins in cervical cancer cells. LY294002 (inhibitor of PI3K/AKT pathway) and IGF-1 (activator of PI3K/AKT pathway) were applied to evaluate the contribution of PI3K/AKT signaling pathway in cervical cancer cells. The expression of SYK(S) in cervical cancer tissues was significantly higher than that of SYK(L). SYK(L) and SYK(S) were correlated with muscular infiltration, SYK(L) high expression had a better prognosis, whereas SYK(S) high expression predicted a worse disease outcome. Cox multivariate regression analysis demonstrated that SYK(L) expression was an independent prognostic factor. SYK(L) significantly inhibited the proliferation, migration and invasion, while SYK(S) showed the opposite effects. LY294002 blocked SYK (L) knockdown-induced enhancement of migration and invasion as well as the expression EMT-related markers, whereas IGF-1 rescued the decreased migration, invasion and EMT induced by SYK (S) knockdown. The results suggest that SYK(L) and SYK(S) are involved in the progression of cervical cancer through PI3K/AKT signaling pathway, and may serve as potential targets for clinical treatment of advanced cervical cancer.